Performance Optimization of Step-Like Divergence Plenum Air-Cooled Li-Ion Battery Thermal Management System Using Variable-Step-Height Configuration - Olanrewaju M. Oyewola; Adetokunbo A. Awonusi; Olawale S. Ismail (Ital Publication, 2024)
Several studies on air-cooled battery thermal management systems (BTMSs) have shown that improvement can be achieved through redesign of the BTMSs. Recent studies have achieved improvements in managing the temperature in the system, but mostly with an increase in pressure drop. It is therefore imperative to carry out an extended study or redesign of the existing designs to overcome these challenges. In this work, a standard Z-type BTMS, which has a flat divergence plenum, was redesigned to have a step-like divergence plenum of variable step height. Computational Fluid Dynamics (CFD) approach was adopted to investigate the thermal and airflow performance of the BTMSs. The CFD methodology was validated by comparing its results with experimental data in the literature. Various step height configurations were considered for 3-step and 4-step models. Findings from the result revealed that the variable step height design enhances the cooling performance of the battery pack. For instance, a 3-step model with step heights of 3, 6, and 6 mm offered the least pressure drop and maximum temperature difference, and when compared with the model with a constant step height of 5, 5, and 5 mm, it yielded reductions of 3.4% and 21.6%, respectively. By increasing the inlet airflow velocity, the 4-step cases generally improved. The best cooling improvement was seen in case 26 at velocities over 3.7 m/s for maximum temperature and velocities over 4.8 m/s for maximum temperature difference. Doi: 10.28991/ESJ-2024-08-03-01 Full Text: PDF